2014
DOI: 10.1186/1746-6148-10-110
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biodegradation of cyanotoxins in the rumen fluid of cattle

Abstract: BackgroundIn countries around the Baltic Sea grazing ruminants have access to and drink, surface water from lakes, rivers and in several coastal regions. The water quality of these naturally occurring reservoirs affects performance and health of livestock. In the Baltic Sea both microcystin (MC) and nodularin (NOD) occurs as cyclic peptides and have hepatotoxic effects. Although cattle obviously have died after consuming contaminated water very little information is available as to how susceptible ruminants ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…This remarkable action produced by LAB in CYN reduction in vegetables is in agreement with that previously reported in cooked fish, and even non detected values were shown in the boiled fish (Maisanaba et al, 2017). Manubolu et al (2014) also described the potential of rumen microorganisms to reduce microscystins and nodularin, suggesting that the microbial flora may preserve or protect against cyanotoxin intoxication.…”
Section: Discussionsupporting
confidence: 91%
“…This remarkable action produced by LAB in CYN reduction in vegetables is in agreement with that previously reported in cooked fish, and even non detected values were shown in the boiled fish (Maisanaba et al, 2017). Manubolu et al (2014) also described the potential of rumen microorganisms to reduce microscystins and nodularin, suggesting that the microbial flora may preserve or protect against cyanotoxin intoxication.…”
Section: Discussionsupporting
confidence: 91%
“…Cyanotoxins produced by cyanobacteria may pose a threat to animals due to their widespread occurrence in both fresh and sea waters [32]. In spite of a recent study indicate that rumen microorganisms may degrade several cyanotoxins [33], the threat from cyanotoxins cannot be ignored. Our results revealed that BSS might inhibit the growth of cyanobacteria, since its antibacterial activity has been documented [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…This increase is problematic because excessive cyanobacteria can both directly and indirectly degrade ecosystem services vital to humans (Saqrane and Oudra, 2009). One prominent negative feature of cyanobacteria blooms is the production of toxins that can reduce the availability of clean, safe water for recreation (e.g., swimming), human and livestock consumption, and crop irrigation (Brooks et al, 2016;Manubolu et al, 2014;Lee et al, 2017b;Saqrane and Oudra, 2009). Among the many types of cyanotoxins that have been documented, microcystin (MC), a liver toxin, is the most frequently occurring in freshwater environment, and hence, has been widely investigated (An and Carmichael, 1994).…”
Section: Introductionmentioning
confidence: 99%